OPTIMISATION AND MODELING OF FLUORIDE REMOVAL BY ELECTROCOAGULATION IN A CONTINUOUS FLOW BIPOLAR REACTOR - Benderrah, T.; Djedid, M.; Naceur, M. W.; Benalia, M. (Journal of Fundamental and Applied Sciences, 2021)
In this study an experimental design was employed to investigate the effects of different operating conditions on the removal of fluoride by electrocoagulation with aluminum electrodes. Box-Behnken design was then used for optimizing and modeling the electrocoagulation process and for evaluating the effects and interactions of variables: current density (i, A/m2), flow rate (Q, mL/min), and initial fluoride concentration (C0, mg/L). The proposed model fitted very well with the experimental data. R2 adjusted correlation coefficients (AdjR2: 0.98) for fluoride removal efficiency showed a high significance of the model. The model predicted for a maximum removal of fluoride (95.07%) at the optimum operating conditions (120 A/m2, 120 mL/min and 30 mg/L) after the EC process was 94.76% at the same optimum operating conditions.